Comprehensive Study of the Enzymatic Catalysis of the Electrochemical Oxygen Reduction Reaction (ORR) by Immobilized Copper Efflux Oxidase (CueO) From Escherichia coli - Chumillas, Sara; Maestro, Beatriz; Feliu, Juan M.; Climent, Víctor (Frontiers in Chemistry, 2018)
In recent years, enzymatic fuel cells have experienced a great development promoted by the availability of novel biological techniques that allow the access to a large number of enzymatic catalysts. One of the most important aspects in this area is the development of biocatalysts for the oxygen reduction reaction (ORR). Laccases from the group of enzymes called blue multi-cooper oxidases have received considerable attention because of their ability to catalyze the electrochemical oxygen reduction reaction to water when immobilized on metallic or carbonaceous electrode materials. In this paper we report a comprehensive study of the electrocatalytic activity of electrode immobilized enzyme CueO from E.Coli. Influence of the electrode substrate employed for protein immobilization was evaluated using glassy carbon, gold or platinum electrodes. Gold and platinum electrodes were modified using different self-assembled monolayers (SAM) able to tune the electrostatic interaction between the protein and the substrate depending on the nature of the terminal functional group in the SAM. Effect of protein immobilization time, electrode potential, solution pH and temperature, protein and O2 concentration have been carefully investigated. Finally, direct electron transfer was investigated in the presence of inhibitors such as fluoride (F-), chloride (Cl-) and azide (N3-).